JURIDICAL REVIEW OF THE ROLE OF THE POLICE OF THE REPUBLIC OF INDONESIA IN LAW ENFORCEMENT IN THE CASE OF STUDENT BRAWLS ON THE STREET OF STRUGGLE - Gina Nurfaidah; Nabilatus Sabila; Chabibaturrochbiyyah Chabibaturrochbiyyah; Anom Sutrisno (Ann Publisher, 2025)
Abstract. Background. Brawls between students in Indonesia, especially in Cirebon City, especially on Jalan Perjuangan, Kesambi District, have disturbed the community. Brawls are triggered by the desire to show strength or defend the group, which even damages the community. Aims. This study aims to analyze the role of the Kesambi Cirebon City Police in handling cases of brawls between students and the law enforcement efforts carried out. Methods. The research method is an empirical juridical approach with qualitative and descriptive techniques. The data was obtained through interviews with police officers and the public. Result. The study's results show that the Kesambi Cirebon City Police have made preventive and repressive efforts, such as the Police Goes to School program and student raids. Conclusion. However, preventive and repressive efforts have not been able to overcome the root of the problem of student brawls comprehensively. Implementation. To effectively and sustainably address the problem of student brawls, a more comprehensive approach involving character education, stricter supervision, and stricter law enforcement is needed.